2022
DOI: 10.1192/bjo.2022.546
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners’ experience of the working alliance in a blended cognitive–behavioural therapy intervention for depression: qualitative study of barriers and facilitators

Abstract: Background Digital technologies have been widely acknowledged as a potentially useful resource for increasing mental healthcare access. The working alliance is a key influence on outcomes in conventional psychotherapy, but little is known about therapists’ experiences of forming an effective working alliance in blended interventions that involve in-person psychotherapy and a digital programme. Aims To investigate psychological well-being practitioners’ (PWPs’) experiences of the working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…While considering what may have facilitated higher levels of adoption and feasibility, this project suggested that the versality and multicomponent design, rather than the complexity, of DMHIs is important as evidenced by the diversity of responses to how clinicians and patients imagined the DMHI could be used to align with treatment goals. This is reflective of similar findings, which found that approaching DMHI development from a versatile rather than a complex perspective may be preferable [ 21 ]. Results from the case examples and follow-up survey responses also suggest that DMHI autonomy is important to allow the DMHI to appropriately align and augment the unique clinical styles of clinicians and the needs of patients, which has also been evident in other recent findings [ 22 ].…”
Section: Discussionsupporting
confidence: 57%
“…While considering what may have facilitated higher levels of adoption and feasibility, this project suggested that the versality and multicomponent design, rather than the complexity, of DMHIs is important as evidenced by the diversity of responses to how clinicians and patients imagined the DMHI could be used to align with treatment goals. This is reflective of similar findings, which found that approaching DMHI development from a versatile rather than a complex perspective may be preferable [ 21 ]. Results from the case examples and follow-up survey responses also suggest that DMHI autonomy is important to allow the DMHI to appropriately align and augment the unique clinical styles of clinicians and the needs of patients, which has also been evident in other recent findings [ 22 ].…”
Section: Discussionsupporting
confidence: 57%
“…Policy makers need also to consider factors outside the clinic in order to integrate these technologies more fully into the mental healthcare system. These include providing proper reimbursement for their use and the costs of staffing and infrastructure, in order to ensure successful implementation and continued use 1 30…”
Section: Presentationmentioning
confidence: 99%
“…The 6-week bCBT intervention comprised 6 face-to-face individual CBT sessions via videoconferencing combined with the depression or anxiety module of the app. Although there are some qualitative studies covering health care providers’ [ 40 ] and patients’ experiences with bCBT [ 41 ] as well as with stand-alone iCBT [ 54 ], this study is, to our knowledge, the first to investigate factors related to the use (and nonuse) of an app within a bCBT program among students.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to increase treatment uptake among students with depression or anxiety symptoms, there is a need for bCBT approaches that fit therapists’ as well as patients’ needs and preferences [ 39 ]. A few studies have focused on therapists’ perspectives regarding their expectations for and experiences with bCBT [ 38 , 40 ], but to date, there is little qualitative research on patients in general and with students in particular. A study by Etzelmueller et al [ 41 ] reported predominantly positive experiences with a bCBT program among patients with major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%